Genotype- and phenotype-directed antiplatelet therapy selection in patients with acute coronary syndromes. (November 2014) - Ismail, Sahar; Lee, Yee Ming; Patel, Meet; Duarte, Julio D; Ardati, Amer K
<x xml:space="preserve">Abstract</x> Although dual antiplatelet therapy (DAPT) has been a standard treatment in patients with acute coronary syndrome (ACS) for over a decade, only recently have therapeutic options beyond aspirin and clopidogrel become available. Additional treatment options are particularly useful because of the documented history of variability in antiplatelet response. This article reviews the current treatment options for DAPT in ACS, and reviews both genotype- and phenotype-guided methods for determining optimal antiplatelet therapy for patients with ACS. Additionally, recommendations from current guidelines as well as expert commentary are provided for the use of available testing methods to determine optimal DAPT for ACS patients.